"Good care" throughout the prostate cancer pathway: Perspectives of patients and health professionals. (October 2019) - Appleton, Rebecca; Nanton, Veronica; Roscoe, Julia; Dale, Jeremy
Abstract: Purpose: Men in follow up for prostate cancer represent the largest proportion of patients with the illness. In the United Kingdom, primary care is increasingly involved in caring for these patients. Little is known however regarding the factors that determine men's evaluation of their care and primary healthcare professionals' perceptions of the care they provide. This study aimed to investigate patient and primary care based health professionals' perspectives of what constitutes 'good care' for men with prostate cancer, including limiting or facilitating factors. Method: Semi-structured interviews were conducted with ten patients and eight primary care based healthcare professionals and thematically analysed in collaboration with a patient representative group. Results: Good care was identified by patient participants, with aspects of communication, including information, active participation, sensitivity of approach and context being highlighted. Healthcare professionals also prioritised communication as the basis of good care and recognised the benefits of locally based services. Conclusions: Treatments in prostate and other cancers continue to improve with corresponding increases in survival. To further develop and sustain the good care that patients require to help them cope with diagnosis, treatment and long term adjustment, investment in resources, training and innovative communication systems between patients, generalist and specialist services are required. Highlights: Effective communication was viewed by both patients and professionals as vital to good care. Clinicians should do more to help men talk about sensitive topics. Professionals recognised a preference for follow up care to be based at a general practice. To provide optimum primary based care, more resources and training are needed.